A multi-layer data grid model for IT platform of a geographically distributed organization - Chuvakov, Aleksandr; Pirova, Diera; Ivaschenko, Anton; Avsievich, Alexandr; Avsievich, Vladimir (AIP conference proceedings, 2023)
Modern approaches of organizational management of multi-corporate enterprises require implementation if IT platforms capable of processing of Big Data in real time. This trend deals with the problems of organization of unstructured data storage and digital processing. In this paper there is proposed a new multi-layer data grid model for an IT platform of a geographically distributed organization. Considering the specifics of such type of organizations the data grid model is divided into three levels: the level of performers, the level of local nodes and the level of the coordination center. Each level considers the possibility for balancing of work between the elements of the system subject to their efficiency. The proposed solution was probated and illustrated in this paper by an example of fifth party transportation logistics automation.